Komparasi Komitmen BSI dan Bank Muamalat dalam Pencapaian SDGs - Maula Ristya; Ahmad Fauzan Mubarok; Miswan Ansori (Jurnal Iqtisad, 2025)
Islamic banking, as an Islamic financial institution, is not solely profit-oriented but also holds a social responsibility to enhance societal welfare in accordance with the maqasid sharia principles. These principles align with the Sustainable Development Goals (SDGs). This study aims to assess the commitment of Islamic banking institutions to achieving the SDGs by employing a quantitative descriptive approach with time-series analysis. The analyzes data trends over a specified period using secondary data obtained from the sustainability reports of Bank Syariah Indonesia (BSI) and Bank Muamalat for the 2021–2024 period. Data collection involved identifying, downloading, and examining relevant sustainability reports containing information on programs, policies, and initiatives that support the attainment of the SDGs. The findings indicate that, overall, BSI demonstrates a stronger commitment to sustainability and environmentally oriented financing compared to Bank Muamalat, with a greater emphasis on funding for Micro, Small, and Medium Enterprises (MSMEs). In contrast, Bank Muamalat exhibited an increasing trend in financing the medium segment but experienced a significant decline in financing for the micro and small segments. This study reaffirms the contribution of Islamic banking-particularly BSI and Bank Muamalat in supporting the achievement of the SDGs through various strategic sector initiatives. The findings provide valuable insights into the role of Islamic banking in fostering inclusive and sustainable economic development.